Unlocking nature’s treasure-chest: screening for oleaginous algae - Steve Slocombe (Scientific Reports, 2015)
Micro-algae synthesize high levels of lipids, carbohydrates and proteins photoautotrophically, thus attracting considerable interest for the biotechnological production of fuels, environmental remediation, functional foods and nutraceuticals. Currently, only a few micro-algae species are grown commercially at large-scale, primarily for "health-foods" and pigments. For a range of potential products (fuel to pharma), high lipid productivity strains are required to mitigate the economic costs of mass culture. Here we present a screen concentrating on marine micro-algal strains, which if suitable for scale-up would minimise competition with agriculture for water. Mass-Spectrophotometric analysis (MS) of nitrogen (N) and carbon (C) was subsequently validated by measurement of total fatty acids (TFA) by Gas-Chromatography (GC). This identified a rapid and accurate screening strategy based on elemental analysis. The screen identified Nannochloropsis oceanica CCAP 849/10 and a marine isolate of Chlorella vulgaris CCAP 211/21A as the best lipid producers. Analysis of C, N, protein, carbohydrate and Fatty Acid (FA) composition identified a suite of strains for further biotechnological applications e.g. Dunaliella polymorpha CCAP 19/14, significantly the most productive for carbohydrates, and Cyclotella cryptica CCAP 1070/2, with utility for EPA production and N-assimilation.